Translingual Academic Writing at Internationalised Universities: Learning From Scholars - Brinkschulte, Melanie; Grieshammer, Ella; Stoian, Monica Elena (Journal of Academic Writing, 2018)
Due to the internationalisation of universities and the globalisation of academic cultures, academic writing is influenced by several writing traditions, heterogeneous reader expectations, as well as internal and external multilingualism. The programme MultiConText (Multilingual Writing in Academic Contexts) at the International Writing Centre at Göttingen University offers a pedagogical approach which deals with these aspects and aims at fostering writing skills for international, multilingual contexts. Writing workshops within the programme target students of all faculties, especially students of international study programmes. The pedagogical approach takes into account Canagarajah’s (2013) idea of translingual practice and the concept of language repertoires (Busch 2017), encouraging students to use all available language codes as a resource in writing. In order to strengthen this approach’s foundation, interviews with scholars working in international research teams were conducted. These interviews focused on the strategies scholars use when writing for publication, especially those for writing in multilingual contexts. Results from the interviews were adapted for classroom use to show students a variety of possibilities to deal with multilingualism in writing. This article makes a suggestion as to how theoretical concepts of multilingualism may be investigated in interviews and how they might be put into practice in writing assignments.